2018
DOI: 10.1038/s41433-018-0033-3
|View full text |Cite
|
Sign up to set email alerts
|

The thick and thin of the central corneal thickness in glaucoma

Abstract: Central corneal thickness (CCT) is an important parameter in the assessment of any potential glaucoma patient. While it affects prognosis in ocular hypertension, its value in patients diagnosed with glaucoma is less certain. There are several biological factors and genetic components that may influence glaucoma progression, which have been associated with thinner CCT. The CCT itself can be affected by several factors including ethnicity, age, sex, glaucoma medications, genetics, and the subtype of glaucoma. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 111 publications
(136 reference statements)
2
49
0
1
Order By: Relevance
“…Corneal thickness is associated with IOP. As for IOP measurement, thicker cornea results in higher IOP than thinner cornea [19,20]. In eyes with thicker cornea, postoperative IOP after trabeculectomy might be overestimated compared to the actual IOP.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal thickness is associated with IOP. As for IOP measurement, thicker cornea results in higher IOP than thinner cornea [19,20]. In eyes with thicker cornea, postoperative IOP after trabeculectomy might be overestimated compared to the actual IOP.…”
Section: Discussionmentioning
confidence: 99%
“…A worldwide meta-analysis found that the average CCT for normal eyes derived from various racial groups, regardless of the device used, was 544 μm [ 21 ], a value that is thinner than that for the Jordanian population we studied (550 μm). Comparing CCT values of our Jordanian population with Caucasian ethnicity, the most represented ethnicity in ethnicity-comparing studies [ 22 ], Caucasian ethnicity mean CCT was similar to Jordanian’s (550 ± 30.5 μm) [ 23 ]. On the other hand, African ethnicity has a lower CCT than that for Jordanians (514.77 ± 31.86) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, African ethnicity has a lower CCT than that for Jordanians (514.77 ± 31.86) [ 23 ]. It should be noted that the technique used to measure CCT can affect the results [ 24 ], and although the results from commonly used devices mostly correlate, the direct comparison between them might not be accurate [ 22 ], so that we will only include studies that used similar techniques for direct value comparison purposes. Regarding CCT difference between different glaucoma types, only PACG eyes have thinner corneas compared to POAG, PXFG, and control eyes, This comes in accordance with what a recent study suggested, where no difference in corneal thickness between POAG, PXFG, and control eyes was found [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, important correlations between corneal pachymetry and glaucoma have emerged unequivocally, due to the diffusion of refractive surgery and the related pre-op tests. Considering that the CCT in normal conditions is just over half a millimeter (540 ± micron), patients with thin cornea have a higher risk of development and progression of glaucomatous damage, while those with thick cornea are more protected from glaucomatous risk ( Figure 6) (Gaspar et al, 2017;Belovay and Goldberg, 2018). However, it is important to remember that measurement of IOP by standard techniques is lower than the real value in patients with thin cornea and higher in those with thick cornea.…”
Section: Glaucoma Diagnosismentioning
confidence: 99%